Prevalence of oral potentially malignant disorders associated with habits in Puducherry - Swetha Paulose; Vishwanath Rangdhol; Lakshminarayanan Kavya; Govindasamy Ezhumalai (Universidade Estadual de Campinas, 2020)
Tobacco and betel quid are the most common cause of oral cancer in India. Very often oral cancers are preceded by a visible oral precursor lesion called as potentially malignant disorder (PMD). Aim: The aim of this study was to assess the prevalence of oral PMDs associated with habits in urban and rural areas of Puducherry Union territory, India. Methods: A cross-sectional descriptive study in urban and rural areas of Puducherry was conducted. The study group comprised of 450 patients with positive history of oral habits. A standard structured questionnaire was designed to record information about demographic details, socioeconomic status, type, duration and frequency of habits followed by clinical oral examination by single trained and calibrated examiner to detect the presence of PMD. Statistical analysis used: EpiData software (version 3.1). Descriptive statistics were presented for all variables. Pearson's Chi-Square test and adjusted odds ratio (ORs) with 95% confidence interval (CI) were calculated to estimate the suspected risk factors for PMD by using multivariate logistic regression analysis. P-value of ≤ 0.05 was considered to be statistically significant. Results: Prevalence of habit associated oral PMD was 64.2%. Females were more prone to develop PMDs (68.3%) as compared to males (62.8%). PMD was more common in the age group of 51-60 years (69.2%). Smoking with alcohol consumption was the most common oral habit. Habits, socio-economic status and diet were significantly associated with development of oral PMDs in our study population. Multivariate logistic regression analysis showed that chronic betel quid chewing and smoking were significant risk factors for PMD. Increased frequency of vegetable consumption reduced the risk of PMD. Conclusions: Oral PMD were observed in more than half of the subjects with oral habits in Puducherry. Clearly, there is an increased risk of PMD with increased duration of tobacco and betel quid use in this region. Patients and public need to be educated regarding PMD and encouraged to quit habits so as to prevent high risk population from developing cancer.